PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPS DENGAN METODE PROBLEM SOLVING DI SEKOLAH DASAR - Herawati, Desi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This research aim was to describe improve learning achievement for students with problem solving methods at the primary school in Pakan Labuah Bukittinggi. This study was a classroom action research Consisting of two cycles. Each cycles consisted of planning, action, observation, and reflecting. The Data Analyzed by using qualitative and quantitative approach. The subject at class IV students of SDN 03 Pakan Labuah Bukittinggi with 25 students. The result of the research Showed improve learning achievement with problem solving method. Kata kunci :  hasil belajar siswa; metode problem solving